Response of several Tree Species to Management on Degraded Soil of Semi-arid Region - Gupta, G. N.; Mohan, S. (Indian Forester, 1990)
A field experiment on skeletally, degraded forest land of a semi-arid region revealed that adoption of water harvesting technique coupled with preplant applicafion of 25 g each of urea and single superphosphate per plant increased the early growth of tree species of the 11 tree species tried, 7 responded dramatically to management. The increase in biomass yield varied from 5 times to 22 times The most suitable tree species, in order of their performance, on these wastelands were P. pterocarpum, E comaldulensis, A. planifrons, A. nilotica, C. pentandra, A. lebbek and A. leucnophloea. Root growth of these tree species also increased many folds owing to the management treatment.